MODERN SURGICAL TREATMENT OF GAS GANGRENE - Matmurotov K.J; Ismailov U.S; Yakhubov I.Y; Yorkulov A.Sh; Kosimov N.A (Scholar Express Journals, 2025)
Presented article displays the work, containing review and analysis of modern literature and textbooks, which contains the most important information about the gas gangrene – a dangerous infection of the battlefield, which could sometimes occur in a peaceful time
Keywords: gangrene; surgery; Pirogov